2017
DOI: 10.17265/1537-1514/2017.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Emotional Intelligence on Investment Decision Making With a Moderating Role of Financial Literacy

Abstract: This study explores the impact of emotional intelligence on investment decision making with a moderating role of financial literacy. The data are collected by using convenient sampling technique through a 5-point Likert scale questionnaire from a sample of 160 investors from stock exchange and banks. We found a positive and significant relationship between emotional intelligence and investment decision making and the same between financial literacy and investment decision. In addition, when we examined these t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…Very few studies have focused on behavior and portfolio diversification (Shinagawa, 2014;Jacobs, Muller, & Weber, 2014;Fuertes, Muradoglu, & Ozturkkal, 2012;Mouna & Anis, 2015). In addition, few studies have been conducted in Pakistan slightly related to this study (Ghaffar & Sharif, 2016a;Awais, Laber, Rasheed, & Khursheed, 2016;Hadi, 2017). But to the best of our search and knowledge, very rare studies can be found on this topic, particularly in developing country like Pakistan.…”
Section: Introductionmentioning
confidence: 90%
“…Very few studies have focused on behavior and portfolio diversification (Shinagawa, 2014;Jacobs, Muller, & Weber, 2014;Fuertes, Muradoglu, & Ozturkkal, 2012;Mouna & Anis, 2015). In addition, few studies have been conducted in Pakistan slightly related to this study (Ghaffar & Sharif, 2016a;Awais, Laber, Rasheed, & Khursheed, 2016;Hadi, 2017). But to the best of our search and knowledge, very rare studies can be found on this topic, particularly in developing country like Pakistan.…”
Section: Introductionmentioning
confidence: 90%
“…Effect of Emotional Quotient (EQ) on Investment Performance or Decisions Emotion and perceptions are critical components of behavioral finance that significantly influence the decision-making processes of investors. Several studies have been conducted in the past to examine whether emotional quotient positively affects the investment performance and decisions (Tanvir, Sufyan & Ahsan, 2016;Dhiman & Raheja, 2018;Sashikala & Chitramani, 2017;Pirayesh, 2014;Hadi, 2017;Tariq & Hassan, 2017;Dhiman & Raheja, 2018). Tanvir, Sufyan, and Ahsan (2016) examined the impact of an investor's emotional intelligence on investment decisions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The emotions from past experiences, for instance, may override rational thinking when making decisions (Hadi, 2017;Charles & Kasilingam, 2014). Investors are likely to be driven by their emotions based on past performances.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, secondary markets known as capital markets works through stock exchanges in the economies and provides investment opportunities in various financial instruments like bonds, stocks, shares and securities (Shahbaz et al, 2015). Past studies have been conducted to check the impact of financial litearcy on investment decisions in various sector of the economy (Ahmad & Ali, 2020;Hadi, 2017;Rooij, Lusardi, & Alessie, 2011).…”
Section: Introductionmentioning
confidence: 99%